2022
DOI: 10.1001/jamanetworkopen.2022.24478
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy After Chemotherapy and Radiation for Clinical Stage III Lung Cancer

Abstract: IMPORTANCEThe 2017 international PACIFIC trial established a role for immunotherapy after chemoradiation for unresectable stage III non-small cell lung cancer (NSCLC). However, in the US, patients with NSCLC commonly differ from clinical trial populations in terms of age, health, access to care, and treatment course, which may all factor into the efficacy of immunotherapy. OBJECTIVETo determine the outcomes of immunotherapy use in unresectable stage III NSCLC in the general US population. DESIGN, SETTING, AND … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Using radiation to make tumors susceptible to drugs that did not work before treatment may provide a highly impactful new role for radiation as we have observed in vitro ( 10, 22, 34, 38 ). Radiation priming strategies are being studied in close proximity to immunotherapy ( 46, 47 ). The short-term data in this experiment and our long-term in vitro data indicate immunologic adaptation which may provide additional opportunities for immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Using radiation to make tumors susceptible to drugs that did not work before treatment may provide a highly impactful new role for radiation as we have observed in vitro ( 10, 22, 34, 38 ). Radiation priming strategies are being studied in close proximity to immunotherapy ( 46, 47 ). The short-term data in this experiment and our long-term in vitro data indicate immunologic adaptation which may provide additional opportunities for immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…PACIFIC trial data showed a significant improvement in progression-free survival (PFS) and overall survival (OS) with durvalumab in patients with inoperable stage III disease treated with concurrent chemoradiation [15]. A real-world study also showed that consolidation with immunotherapy led to better survival even in patients treated outside the PACIFIC trial protocol [16]. In this article, we provide an overview of the treatment of stage III NSCLC, particularly focusing on the recent advancements in the last 5 years.…”
Section: Introductionmentioning
confidence: 99%